Taxonomic notes on the Lycocerus purpurascens species-group (Coleoptera: Cantharidae), with descriptions of two new species from China - Yang, Zheng; Liu, Hao-Yu; Yang, Xing-Ke; Yang, Yu-Xia (Zootaxa, 2026)
The Lycocerus purpurascens species-group is redefined. Lycocerus purpurascens (Wittmer, 1978) is redescribed in detail. Another four species are assigned to this species-group, including L. safraneki (Švihla, 2004), L. benesi (Švihla, 2004), L. nigromaculatus sp. nov. (Sichuan, Chongqing, Hubei, Shaanxi) and L. medogensis sp. nov. (Xizang). These species are illustrated with habitus, aedeagus, as well as abdominal sternite VIII and internal reproductive organs of female. An identification key and a distribution map of the species-group are provided.